PENGARUH FREE CASH FLOW, PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN - Muhammad Asril Arilaha (University of Merdeka Malang, 2009)
The objective of the study was to provide empirical evidence about the effect offree cash flow, profitability, liquidity and leverage toward dividend policy. The population ofthis study was manufacture companies listed in Indonesian Stock Exchange in 2004 2007. Thesampling technique used purposive sampling and the analysis method used was multipleregressions. The result of this study proved that the profitability of a company affected thedividend policy. The bigger company profit was, the bigger dividend share was. A companywhich had profit stability could settle on dividend payment rate certainly and signal the qualityof their profit. While, free cash flow, liquidity and leverage had no effect toward dividend.